Leadership in Disaster: A Global Challenge For Nurse - Iswanto; Priyanti, Ratna Puji; Asri; Batubara, Sakti Oktaria (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Nurse is well known as a leader in compassionate profession that always take part in every crisis and emergency situation. Nurse mostly force to be a leader without formal education as a leader. This paper is to explore the leadership in disaster nursing as a challenge today and in the future. As a leader nurse must have certain knowledge and ability in decision making, communication and collaboration to manage the catastrophe events. Nurse must have certain traits and characteristics to manage the presence and influence as a leader and an ability to understanding the right leadership style that appropriate within the situation in crisis. Connecting the requirement of leadership in disaster nursing with the standardized curricula of leadership in disaster nursing is the future recommendation for nursing scholar.